Struktura i soderzhanie mnogoletnei podgotovki sportivnogo reserva v futbole - Zolotarev, A. P. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
For better results in football it was caried out a study to create a new conception for effective long term planning in age-group football. The main points of a rational training structure in children and youth football are pointed out.